Robotic Liver Surgery – Current Standards and Future Perspectives - Becker, Felix; Morgül, Haluk; Katou, Shadi; Juratli, Mazen; Hölzen, Jens Peter; Pascher, Andreas; Struecker, Benjamin (Zeitschrift für Gastroenterologie, 2021)
Background Robotic liver surgery is emerging as the future of minimal invasive surgery. The robotic surgical system offers a stable camera platform, elimination of physiologic tremor, augmented surgical dexterity as well as improved ergonomics because of a seated operating position. Due to the theoretical advantages of the robotic assisted system, complex liver surgery might be an especially interesting indication for a robotic approach since it demands delicate tissue dissection, precise intracorporeal suturing as well as difficult parenchymal transection with subsequent need for meticulous hemostasis and biliostasis.Material and methods An analysis of English and German literature on open, laparoscopic and robotic liver surgery was performed and this review provides a general overview of the existing literature along with current standards and aims to specifically point out future directions of robotic liver surgery.Results Robotic liver surgery is safe and feasible compared to open and laparoscopic surgery, with improved short-term postoperative outcomes and at least non-inferior oncological outcomes.Conclusion In complex cases including major hepatectomies, extended hepatectomies with biliary reconstruction and difficult segmentectomies of the posterior-superior segments, robotic surgery appears to emerge as a reasonable alternative to open surgery rather than being an alternative to laparoscopic procedures.
Keywords: liver; hepatic resection; robotic surgery; minimal invasive surgery; laparoscopy